The role of small extracellular vesicles and microRNA as their cargo in the spinal cord injury pathophysiology and therapy - Sintakova, Kristyna; Romanyuk, Nataliya (Frontiers in Neuroscience, 2024)
Spinal cord injury (SCI) is a devastating condition with a complex pathology that affects a significant portion of the population and causes long-term consequences. After primary injury, an inflammatory cascade of secondary injury occurs, followed by neuronal cell death and glial scar formation. Together with the limited regenerative capacity of the central nervous system, these are the main reasons for the poor prognosis after SCI. Despite recent advances, there is still no effective treatment. Promising therapeutic approaches include stem cells transplantation, which has demonstrated neuroprotective and immunomodulatory effects in SCI. This positive effect is thought to be mediated by small extracellular vesicles (sEVs); membrane-bound nanovesicles involved in intercellular communication through transport of functional proteins and RNA molecules.In this review, we summarize the current knowledge about sEVs and microRNA as their cargo as one of the most promising therapeutic approaches for the treatment of SCI. We provide a comprehensive overview of their role in SCI pathophysiology, neuroprotective potential and therapeutic effect.